Efficient synthesis and characterisation of the amyloid beta peptide, Aβ1–42, using a double linker system. Issue 1 (30th November 2018) - Kasim, Johanes K.; Kavianinia, Iman; Ng, Jin; Harris, Paul W. R.; Birch, Nigel P.; Brimble, Margaret A.
Abstract : The amyloidogenic Aβ42 peptide was prepared in high purity and yield enabling biophysical characterisation studies using a double linker system and the incorporation of pseudoprolines. Abstract : The amyloidogenic Aβ42 peptide was efficiently prepared using a double linker system, markedly improving solubility and chromatographic peak resolution, thus enabling full characterisation using standard techniques. The tag was readily cleaved with sodium hydroxide and removed by aqueous extraction, affording Aβ42 in high purity and yield for biophysical characterisation studies.